Land and water productivity of wheat in the western Indo-Gangetic Plains of India and Pakistan: a comparative analysis - Hussain, I.; Sakthivadivel, Ramaswamy; Amarasinghe, Upali A.; Mudasser, M.; Molden, David J. (International Water Management Institute, 2003)
The purpose of this study is to analyze variations in wheat yields and to assess the range of factors affecting wheat yields and profitability of wheat production in the selected irrigation systems in India and Pakistan. The study attempts to identify constraints and opportunities for closing the existing yield gaps. It is hypothesized that substantial gains in aggregate yields can be obtained by improved water management practices at the farm and irrigation-system levels.